Močnostni spekter nihanja med mirno stojo pri bolnikih s Parkinsonovo boleznijo - Bartolić, Andrej (Medicinski razgledi, 2001)
Parkinson's disease is a slowly progressive, degenerative disorder of the substantia nigra of unknown etiology. The main pathomorphological finding in Parkinson's disease is the loss of dopaminergic neurons in the substantia nigra pars compacta, which results in deficiency of the neurotransmitter dopamine in the striatum. Parkinson's disease is an akinetic-rigid syndrome with the main clinical features of tremor, rigidity, bradykinesia and posturalinstability. Although postural instability has a large impact on the quality of life of Parkinsonian patients, it can be only poorly controlled by antiparkinsonian treatment. Besides Parkinson's disease, postural instability can also result from diseases of the vestibular system, cerebellum, diabetes mellitus, effects of various drugs or aging. The aim of the first part of thisstudy was to measure the maintenance of equilibrium during free stance in a group of young subjects and a group of healthy seniors in order to assess the influence of age on postural stability. The objective of the second part of the study was to measure the maintenance of equilibrium during free stance in a group of patients with Parkinson's disease, before and after administration of the dopaminergic agonist apomorphine. The intention was to establish the influence of apomorphine on postural instability. The maintenance of equilibrium was measured during free stance and the overall motor status was evaluated in healthy subjects and in patients with Parkinson's disease, before and after administration of apomorphine, in order to test the following two hypotheses: 1. The maintenance of equilibrium duringfree stance in healthy subjects (aged 23 to 61) is not affected by age. 2. The dopaminergic agonist apomorphine can significantly change the power spectrum of body oscillations during free stance in patients with Parkinson's disease. (Abstract truncated at 2000 characters).
Keywords: Drža; Parkinson disease; Parkinsonova bolezen; Physiopathology; Diagnosis; Apomorfin; Nevrološka preiskava; Therapy; Posture; Občutek, motnje; Equilibrium; Ravnotežje; Sensation disorders; Statistika neparametrična; Apomorphine; neurology; nevrologija; Neurologic examination; zdravljenje; Statistics, nonparametric